China Technological Transformation: A Case Study of Telecommunications Equipment Industry - Frasminggi Kamasa; Riva'atul Adaniah Wahab (Buletin Pos dan Telekomunikasi, 2021)
China is the world's biggest telecoms equipment exporter. Several telecommunications equipment companies from China dominate the global market, for example, Huawei and ZTE. This study aims to identify factors contributing to China's rapid technological transformation, particularly in the telecommunications equipment industry. In addition, the relationship between the government, SOE, and entrepreneurs is also identified in strengthening the sector. This study uses qualitative and quantitative approaches, data collection through literature study and observation, and data analysis using descriptive data analysis patent analysis, and network analysis. The results show that government technology policy, human resource development and education, foreign technology adoption and adaptation, together with indigenous R & D efforts are essential factors in China's technological transformation process in the telecommunications equipment industry. Due to China’s government's encouragement, SOEs can innovate and encourages the growth of domestic entrepreneurship. Therefore, Indonesia can learn several things from China, including fostering innovation through various strategies such as implementing technology transfer, mentoring with overseas experts, increasing R & D financing support, providing support for industry and researchers in the form of tax incentives or patent subsidies. Furthermore, strengthening collaboration and cooperation with the foreign telecommunications equipment industry with win-win schemes can offer benefits to Indonesia.